Optimasi SMES untuk Load Frequency Control pada PLTMH Menggunakan ICA dan BA - Machrus Ali; Hidayatul Nurohmah; Muhammad Agil Haikal (Universitas Darul Ulum, 2025)
Micro hydro power plants (MHPPs) are increasingly important for decentralized renewable electrification, especially in isolated and rural grids where low inertia makes frequency highly sensitive to abrupt consumer-load variations. The main problem addressed in this study is that governor-turbine dynamics and conventional controller tuning are often insufficient to suppress transient frequency deviation rapidly, while previous MHPP load frequency control (LFC) studies commonly report ICA, BA, SMES, or CES results separately and in per-unit form, making practical comparison less direct. This paper contributes a current benchmark-based synthesis and normalized comparative analysis of Superconducting Magnetic Energy Storage (SMES)-assisted LFC for a 40 kVA, 32 kW, 50 Hz MHPP using the Imperialist Competitive Algorithm (ICA) and the Bat Algorithm (BA) with Integral Time Absolute Error (ITAE) as the optimization objective. Literature benchmark data are reprocessed by converting per-unit overshoot into Hz and by calculating reduction relative to the uncontrolled condition to provide a transparent and reproducible engineering interpretation. ICA-based PID-SMES gives a frequency overshoot of -4.11 x 10^-5 pu (-0.002055 Hz), whereas BA-based SMES-PID gives -4.038 x 10^-5 pu (-0.002019 Hz). Compared with the uncontrolled system, the overshoot reduction reaches 87.07% for ICA and 87.30% for BA. The main contribution of this work is a clarified research-gap map, a normalized ICA-BA comparison on a comparable MHPP benchmark, and a replicable basis for future equal-condition MATLAB/Simulink validation.